Bio-modification and application of coal fly ash in cementitious composites. (December 2022) - Wang, Wenxing; Guo, Shihao; Gu, Xiaowei; Li, Xiaohui; Huang, Weiyu; Li, Ang
Abstract: Coal fly ash (CFA), an industrial solid waste, has been predominantly used a substitute for material in the concrete industry. Its reactivity is usually a crucial factor for use in cementitious composites. Conventionally physical and chemical treatments have been used to modify CFA for improving reactivity, but there still are some limitations such as easy agglomeration of particles, high cost, high energy-consumption, environmental pollution, etc. Herein, a feasible bio-modification treatment on CFA using Paenibacillus mucilaginosus is proposed. Adhesion and desilication of the bacteria & metabolites change the morphology, size distribution and surface properties of CFA. Compared with CFA, the bio-modified CFA (BCFA) has coarser surface, finer particle size, larger specific surface area (SSA), higher surface calcium content and lower surface Si/Al ratio. The characteristic changes contribute to enhancing the reactivity of BCFA relating to morphological, pozzolanic, micro-aggregate and interfacial effects in cementitious composites. The strength activity index (SAI) of BCFA reaches 90.8% at 28 d and increases 27.7% compared to that of CFA. Soluble silicon content in the bioleaching system shows significantly positive correlations with the SSA and SAI of BCFA ( P  < 0.05). The cementitious composites containing 30% BCFA show higher mechanical properties, lower early hydration heat and denser microstructure compared to those containing 30% CFA. This work could provide a promising green and low-carbon way to produce highly active BCFA for concrete industry and other fields.